Enhancing Innovative Work Behaviour among State Civil Apparatus Employees through Leadership and Engagement - Fitri Ayu Lestari; Dewi Kartika Sari; Ahmad Fadillah Putra; Rahmawati Nur Azizah (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
State civil apparatus (SCA) employees in North Kalimantan Province, Indonesia's youngest frontier province, are increasingly required to exhibit innovative work behaviour (IWB) as directed by national innovation policy. Transformational leadership (TFL) and work engagement (WE) are broadly understood to promote such behaviour, yet the moderating role of organisational justice (OJ) in this frontier public sector context remains underexplored. his study aimed to determine the direct influence of TFL, WE and OJ on IWB and to examine whether OJ functions as a moderating variable in these relationships. The study was conducted across regional apparatus organisations in North Kalimantan Province, Indonesia, with a random sample of 480 SCA employees drawn in 2025. Structural equation modelling partial least squares (SEM-PLS) was applied as the analytical method to test causal relationships and moderation effects for each hypothesis. TFL and WE each exerted significant positive direct effects on IWB. OJ, however, did not produce a significant direct effect on IWB and did not function as a moderating variable in any tested relationship. These findings affirm the central role of inspirational leadership and employee engagement in cultivating innovative behaviour within frontier public organisations. OJ, while ethically foundational, does not serve as a catalyst for IWB in this regional government context. This study extends social exchange theory to a frontier provincial context in Indonesia, empirically demonstrating that relational and motivational factors dominate over structural justice perceptions in shaping IWB among SCA employees.